Seed and information exchange through social networks: the case of rice farmers of Indonesia and Lao PDR - Tatlonghari, Gerlie; Paris, Thelma; Pede, Valerien; Siliphouthone, Inpong; Suhaeti, Rita (Scientific Research Publishing, Inc., 2012)
The study investigates the structure of information exchange among men and women farmers who were involved in participatory varietal selection (PVS) on submergence-tolerant varieties in pilot communities in Lao PDR and Indonesia. The paper shows that network relationships influence the dissemination of new information on seed. In their decisions to adopt new rice varieties, farmers are strongly influenced by their kin and friends. The study also investigated social networks by gender in order to gain greater insights into how gender inequalities influence the effectiveness of social capital through social networks. Results show that information opportunities of men and women vary in terms of exposure to and control of information. These differences are mainly influenced by their social and cultural setting in rice farming systems and communities. The paper shows that gender should be accounted for when investigating the determinants of social networks. Factors affecting social networks differ by gender, and also across countries. For instance, older males in Indonesia tend to have larger social networks. Women who belong to large farming households tend to have bigger social networks. Generally, having more relatives is a good opportunity to increase social networks for males and females.